2017
DOI: 10.1371/journal.pone.0183223
|View full text |Cite
|
Sign up to set email alerts
|

Treatment gap and barriers for mental health care: A cross-sectional community survey in Nepal

Abstract: ContextThere is limited research on the gap between the burden of mental disorders and treatment use in low- and middle-income countries.ObjectivesThe aim of this study was to assess the treatment gap among adults with depressive disorder (DD) and alcohol use disorder (AUD) and to examine possible barriers to initiation and continuation of mental health treatment in Nepal.MethodsA three-stage sampling technique was used in the study to select 1,983 adults from 10 Village Development Committees (VDCs) of Chitwa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
125
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

4
5

Authors

Journals

citations
Cited by 121 publications
(134 citation statements)
references
References 56 publications
(64 reference statements)
6
125
3
Order By: Relevance
“…60 Further, somatization is a common presentation of depression in South Asia [61][62][63][64][65] and particularly in Nepal 66 , which could explain the increased demand for physical rather than mental healthcare 56 and might possibly be consistent with the 20% or so who sought care for gastrointestinal symptoms or joint pains (although somatization is a diagnosis of exclusion and we cannot assume that these are not indicative of real underlying pathology). Previous analyses have also shown that only 8.1% of people with probable depression in this sample reported actively seeking treatment specifically for depression symptoms 67 , which is far lower than the 71% who sought any healthcare at all. This may relate to the lack of effective detection and treatment of depression in primary care 68,69 , and possibly to low perceived need for intervention for psychological symptoms.…”
Section: Mechanisms and Implicationscontrasting
confidence: 53%
“…60 Further, somatization is a common presentation of depression in South Asia [61][62][63][64][65] and particularly in Nepal 66 , which could explain the increased demand for physical rather than mental healthcare 56 and might possibly be consistent with the 20% or so who sought care for gastrointestinal symptoms or joint pains (although somatization is a diagnosis of exclusion and we cannot assume that these are not indicative of real underlying pathology). Previous analyses have also shown that only 8.1% of people with probable depression in this sample reported actively seeking treatment specifically for depression symptoms 67 , which is far lower than the 71% who sought any healthcare at all. This may relate to the lack of effective detection and treatment of depression in primary care 68,69 , and possibly to low perceived need for intervention for psychological symptoms.…”
Section: Mechanisms and Implicationscontrasting
confidence: 53%
“…At the time of study, Chitwan had approximately 580,000 residents and a literacy rate of 79%, which is greater than the national average of 68% [28]. Previous research in Chitwan found 11% and 5% of adults screened positive for AUD and depression, respectively [29], while treatment seeking among those who screen positive for either disorder was less than 2% [30]. Within PRIME, PCWs were trained in the detection, assessment, and treatment provision for priority mental disorders.…”
Section: Setting and Participantsmentioning
confidence: 99%
“…Importantly, given that the groups of the Group PM+ intervention will be of a single gender (see details below in Group PM+ intervention) and that we do not have resources to enroll more than one group per ward, we will select a sub-set of 14 of the 72 wards to be those which we enroll male participants and the remaining 58 wards will enroll female participants. This fraction (14/72), close to 20% of all wards, was selected to reflect the anticipated uptake of services which was expected to be lower in this region than in studies conducted by our team in other regions [15,16]. Further, we note that the selection of 14 wards will not be random but instead those 14 wards will be selected to be 14 wards that are close together and that are, nevertheless, representative of the types of wards in the study region.…”
Section: Design and Settingmentioning
confidence: 99%